2017
DOI: 10.1039/c7ra04868h
|View full text |Cite
|
Sign up to set email alerts
|

Effective removal of cesium by pristine graphene oxide: performance, characterizations and mechanisms

Abstract: Cs is effectively removed by graphene oxide (GO). Characterization reveals the Cs capture mechanism by oxygen functional groups and hole defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“… 44 Recent studies demonstrated that the defects in GO sheets are not only always present and often abundant 45 , 46 but also the defects (holes and vacancies) are responsible for some properties important for various applications. 47 49 …”
Section: Introductionmentioning
confidence: 99%
“… 44 Recent studies demonstrated that the defects in GO sheets are not only always present and often abundant 45 , 46 but also the defects (holes and vacancies) are responsible for some properties important for various applications. 47 49 …”
Section: Introductionmentioning
confidence: 99%
“…It can be explained that at pH above 3.9 (pH pzc ), the surface area of GO is partially negatively charged and the electrostatic attractions between cations and GO are stronger because of deprotonation reaction [ 57 ]. It is also caused by the higher availability of active sites on the GO sheets [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was experimentally demonstrated that the maximum adsorption capacity was approximately 528 mg Cs/g of GO. The sorption ability was tuned by adjusting the pH of the medium [40]. An interesting phenomenon was observed when the experiments were carried out under a broad range of pH.…”
Section: ■ Graphene Oxide (Go)mentioning
confidence: 99%